2023
DOI: 10.1002/cmtd.202200075
|View full text |Cite
|
Sign up to set email alerts
|

13C and 15N Benchtop NMR Detection of Metabolites via Relayed Hyperpolarization**

Abstract: Parahydrogen‐based nuclear spin hyperpolarization allows various magnetic‐resonance applications, and it is particularly attractive because of its technical simplicity, low cost, and ability to quickly (in seconds) produce large volumes of hyperpolarized material. Although many parahydrogen‐based techniques have emerged, some of them remain unexplored due to the lack of careful optimization studies. In this work, we investigate and optimize a novel parahydrogen‐induced polarization (PHIP) technique that relies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The study concluded that low‐field benchtop NMRs are not that useful for structure elucidation of complex unknown materials because of their low resolution compared with high‐field NMR spectrometers. In addition, research has been ongoing in low‐field benchtop NMRs to improve their sensitivity for low‐sensitive nuclides through hyperpolarization 70–74 . Poor resolution issues in low‐field NMR can sometimes be ameliorated with chemometrics for structural analysis of molecules with low‐to‐medium complexity.…”
Section: Basic Comparison Of Low‐field Benchtop Nmrs With High‐field ...mentioning
confidence: 99%
“…The study concluded that low‐field benchtop NMRs are not that useful for structure elucidation of complex unknown materials because of their low resolution compared with high‐field NMR spectrometers. In addition, research has been ongoing in low‐field benchtop NMRs to improve their sensitivity for low‐sensitive nuclides through hyperpolarization 70–74 . Poor resolution issues in low‐field NMR can sometimes be ameliorated with chemometrics for structural analysis of molecules with low‐to‐medium complexity.…”
Section: Basic Comparison Of Low‐field Benchtop Nmrs With High‐field ...mentioning
confidence: 99%